Volume and structural relaxation in compressed sodium borate glass. Issue 43 (19th October 2016) - Svenson, Mouritz N.; Youngman, Randall E.; Yue, Yuanzheng; Rzoska, Sylwester J.; Bockowski, Michal; Jensen, Lars R.; Smedskjaer, Morten M.
Abstract : Packing of structural units rather than conversions between them is the main mechanism for pressure-induced densification in sodium borate glass. Abstract : The structure and properties of glass can be modified through compression near the glass transition temperature ( T g ), and such modified structure and properties can be maintained at ambient temperature and pressure. However, once the compressed glass undergoes annealing near T g at ambient pressure, the modified structure and properties will relax. The challenging question is how the property relaxation is correlated with both the local and the medium-range structural relaxation. In this paper, we answer this question by studying the volume (density) and structural relaxation of a sodium borate glass that has first been pressure-quenched from its T g at 1 GPa, and then annealed at ambient pressure under different temperature–time conditions. Using 11 B MAS NMR and Raman spectroscopy, we find that the pressure-induced densification of the glass is accompanied by a conversion of six-membered rings into non-ring trigonal boron (B III ) units, i.e. a structural change in medium-range order, and an increase in the fraction of tetrahedral boron (B IV ), i.e. a structural change in short-range order. These pressure-induced structural conversions are reversible during ambient pressure annealing near T g, but exhibit a dependence on the annealing temperature, e.g. the ring/non-ring B III ratio stabilizes at different values depending on the applied annealing temperature. We find that conversions between structural units cannot account for the pressure-induced densification, and instead we suggest the packing of structural units as the main densification mechanism.